2001
DOI: 10.1046/j.1444-2906.2001.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic animal carotenoids

Abstract: Carotenoids are yellow to red isoprenoid polyene pigments; approximately 650 carotenoids are known from bacteria, fungi, plants and animals. They occur not only as free forms but also as esters, glycosides, sulfates and carotenoproteins. A recent discovery of antitumor activity in carotenoids, such as vitamin A and β‐carotene, has brought attention to marine carotenoids. This review describes the structures of 117 carotenoids isolated from sponges, coelenterates, mollusks, crustaceans, echinoderms, tunicates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
254
0
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(266 citation statements)
references
References 68 publications
1
254
0
11
Order By: Relevance
“…Tunaxanthin (a carotenoid) and drosopterin (a pteridine) are the main pigments in the xanthophores of guppies ; astaxanthin is a common ketocarotenoid found, for example, in crustaceans and salmonid fish (Matsuno, 2001). To human eyes, tunaxanthin is yellow, astaxanthin is orange-red, and drosopterin is red.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Tunaxanthin (a carotenoid) and drosopterin (a pteridine) are the main pigments in the xanthophores of guppies ; astaxanthin is a common ketocarotenoid found, for example, in crustaceans and salmonid fish (Matsuno, 2001). To human eyes, tunaxanthin is yellow, astaxanthin is orange-red, and drosopterin is red.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The main ketocarotenoid in the ZWRI tomato preparation is phoenicoxanthin. Although not abundant in nature, it can be found in mollusks, crustaceans (28), green alga [such as Haematococcus pluvalis (29) and Chlorococcum (30)], and Adonis flowers (31). The synthetic astaxanthin preparations used contain unidentified reaction contaminants and a mixture of stereoisomers, whereas the biosynthetically derived phoenicoxanthin used in the present study was exclusively present in its biologically active S configuration (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Fish and other vertebrates cannot synthesize carotenoids, but they have the ability to change colour under given circumstances (Matsuno 2001). The results of the colour enhancement study suggested that the fishes reared under low level were brighter in colour than other light levels and control.…”
Section: Discussionmentioning
confidence: 74%